Penerapan Media Pembelajaran Pohon Cermat Literasi Untuk Meningkatkan Keterampilan Menganalisis Unsur Intrinsik Teks Cerpen Kelas XI-D2 SMA Negeri 9 Surabaya - Nindita Novi Permatasari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Based on observations in classes XI-D2 of SMA Negeri 9 Surabaya, researchers found that there was a problem in learning, namely the lack of teacher skills in creating an effective learning atmosphere. This condition is the cause of students not being very active in learning, so that the achievement of their learning outcomes in the competence of analyzing the intrinsic elements of short story builders is not good. The focus of this study is to evaluate the effectiveness of the application of the